2016
DOI: 10.18632/oncotarget.11463
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin blockade suppresses sunitinib-resistant renal cell carcinoma growth by targeting the ERK/MAPK pathway

Abstract: PurposeTo evaluate the mechanisms underlying sunitinib resistance in RCC and to identify targets that may be used to overcome this resistance.ResultsReanalysis of transcriptome microarray datasets (GSE64052 and GSE76068) showed that adrenomedullin expression was increased in sunitinib-resistant tumors. And adrenomedullin expression was increased in sunitinib-resistant tumor xenografts, accompanied by upregulation of phospho-ERK levels. However, blocking adrenomedullin inhibited sunitinib-resistant tumor growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…The MAPK signaling pathway is largely implicated in the progression and metastasis of various types of cancer, including RCC (54,55). The p38/MAPK, ERK/MAPK and JNK/MAPK cascades are commonly involved in the malignant progression of RCC (56,57). In addition, previous studies reported an association between increased expression of MMPs and activation of the MAPK signaling pathway (37,58), and between ROS overproduction and activation of the MAPK signaling pathway (22,24).…”
Section: Discussionmentioning
confidence: 98%
“…The MAPK signaling pathway is largely implicated in the progression and metastasis of various types of cancer, including RCC (54,55). The p38/MAPK, ERK/MAPK and JNK/MAPK cascades are commonly involved in the malignant progression of RCC (56,57). In addition, previous studies reported an association between increased expression of MMPs and activation of the MAPK signaling pathway (37,58), and between ROS overproduction and activation of the MAPK signaling pathway (22,24).…”
Section: Discussionmentioning
confidence: 98%
“…In addition to ADM activation upon hypoxia [ 45 51 ], ADM was also shown to act as growth factor, prevent apoptosis-mediated cell death, increase tumour cell motility and metastasis and induce angiogenesis in various cancer types [ 47 49 , 51 , 53 – 59 ]. Of further importance, it has been reported that hypoxia, which can activate ADM [ 45 51 ], induces resistance to ALK inhibitors in non-small cell lung cancer [ 60 ] and that ADM expression levels are increased in tyrosine kinase inhibitor sunitinib resistant renal cell carcinoma [ 61 ]. In view of these observations, we evaluated whether combining an adrenomedullin receptor antagonist (ADM22-52) [ 61 ] together with TAE684 would sensitize NB cells to ALK inhibition.…”
Section: Resultsmentioning
confidence: 99%
“…Of further importance, it has been reported that hypoxia, which can activate ADM [ 45 51 ], induces resistance to ALK inhibitors in non-small cell lung cancer [ 60 ] and that ADM expression levels are increased in tyrosine kinase inhibitor sunitinib resistant renal cell carcinoma [ 61 ]. In view of these observations, we evaluated whether combining an adrenomedullin receptor antagonist (ADM22-52) [ 61 ] together with TAE684 would sensitize NB cells to ALK inhibition. No additional effects on decrease in cell viability were observed (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies have implicated that activating the ERK/MAPK pathway could promote tamoxifen‐resistance in ER+ breast cancer (Heckler, Thakor, Schafer, & Riggins, ), whereas, blockading the ERK/MAPK pathway suppressed sunitinib‐resistant RCC growth (Gao. et al, ). Therefore, the results of GO analysis indicated several significant biological processes, cellular components and molecular functions which might be related with the initiation and development of sunitinib resistance in RCC.…”
Section: Discussionmentioning
confidence: 99%